Production of Natural Hand Sanitizer: An Affordable Solution for Covid-19 Prevention - Fauzi, Muh Ali; Syamsudin, Nur; Mahasinini, Farid Fi; Lestari, Veronika Nugraheni Sri; Solaeman, Najib Ahmad (STAI Miftahul ULa Nganjuk, 2025)
This community service program addresses the challenge of limited access to hand sanitizers in local communities during the COVID-19 pandemic by applying the ABCD (Asset-Based Community Development) approach. The program leverages local resources, specifically betel leaves and lime, to produce affordable and sustainable natural hand sanitizers. The method involves the collection of these natural ingredients, followed by the formulation and production of hand sanitizers, which are then distributed to the community. The program also includes educational initiatives, such as workshops and demonstrations, to teach the community how to create and use hand sanitizers effectively. The results show a significant increase in the community's awareness of hand hygiene and the adoption of healthier behaviors. This initiative empowered local residents to become more self-reliant in maintaining hygiene, thereby contributing to the collective effort in preventing the spread of COVID-19.